Epidemiologic, Clinical and Mycological Profile of Onychomycosis in the Hospital Setting in Benin - Fabrice Akpadjan; Yolande Sissinto Savi De Tove; Aminath Fèmie Tidjani; Cordule Balola; Laura Dotsop; Bérénice Degboe; Nadège Agbessi; Christiane Koudoukpo; Hugues Adegbidi; Félix Atadokpede; Florencia do Ango-Padonou (Dermatology Research and Practice)
Conclusion: Onychomycosis is relatively uncommon in hospitals in Benin. This is underestimated because most patients with a clinical suspicion of onychomycosis do not undergo a mycological examination before being put on antifungal treatment.